The Question of the End Effector of Ischemic Preconditioning of the Heart - Tsibulnikov S. Yu. Sergey Yurjevich; Maslov L. N. Leonid Nikolaevich; Tsepokina A. V. Anna Viktorovna; Khutornaya M. V. Maria Vladimirovna; Kutikhin A. G. Anton Gennadievich; Tsibulnikova M. R. Margarita Radievna; Nam I. F. Irina Feliksovna (2017, 2017)
Title screen